Customer satisfaction on services and facilities rendered by Johor Port Berhad / Zuraimi Abdul Aziz - Abdul Aziz, Zuraimi (2003)
Johor Port Berhad (JPB) provides an effective balance of physical facilities and services to meet every needs and wants of its customers. In addition to proving for traditional and continuing needs of conventional cargo trades, JPB has responded major technological changes in marine transportation and associated cargo-handling system. In order to offer only the best services to its customers, new facilities have been built to meet the modern demands of containerization and other forms of unit load as well as the continued trends towards bulk cargo. As the service provider, it is imperative that JPB meets the expectation of its customers on a continuing basis, thus identifying the customer satisfaction is important. This is to retain the existing customers as well as to attract new customers to make cargo transaction through its port. By increasing level of efficiency in cargo handling in JPB, it will benefit both JPB and its customers. As a result, JPB will gain more profit and customer will not plan to switch to another ports. This research will provide good insights on the level of satisfaction among the JPB customers involving Shipping Agency, Forwarding Agency, Warehouse, Manufacturing, Supplier / Vendors and Haulage Company. The research will analyze attributes on customer satisfaction based on 3 variables rendered by JPB which are: Facilities, Services and Process / Procedure. From the findings has the researcher can conclude that most of customers are satisfied with the services and facilities rendered by JPB. However, JPB needs to improve on certain areas as to increase the level of satisfaction to a maximum level in order to provide more efficient in rendering its services to the customers as well as to compete with its competitors.